Dr. João Amorim — Deep Plane Facelift - Amorim, João (DEEPPLANE™, 2026)
Surgeon profile record for Dr. João Amorim, Brazil. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003100; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; brazil